Interplay between RGS2 and childhood adversities in predicting anxiety and depressive disorders: Findings from a general population sample. Issue 11 (14th August 2018) - Asselmann, Eva; Hertel, Johannes; Schmidt, Carsten‐Oliver; Homuth, Georg; Nauck, Matthias; Beesdo‐Baum, Katja; Grabe, Hans‐Jörgen; Pané‐Farré, Christiane A.
Abstract : Background: It remains unresolved whether childhood adversities interact with genetic variation in regulator of G‐protein signaling 2 ( RGS2 ) rs4606 in predicting various anxiety and depressive disorders and whether diagnostic specificity exists in these interactions. Methods: The genotype of RGS2 rs4606 was determined for N = 2, 263 adults with European ancestry from the Study of Health in Pomerania. Lifetime anxiety and depressive disorders according to the Diagnostic and Statistical Manual of Mental Disorders, fourth edition, were assessed with the Munich Composite International Diagnostic Interview (DIA‐X/M‐CIDI). Childhood adversities were assessed with the Childhood Trauma Questionnaire (CTQ, when participants were aged 29–89). Results: Logistic regressions adjusted for sex and age revealed that rs4606 interacted with total childhood adversity in predicting each diagnostic outcome except for panic disorder and generalized anxiety disorder, uncorrected and corrected for multiple testing (odds ratio [OR] = 1.06–1.16). That is, carriers of the GG (vs. CC/CG) genotype were at decreased risk for anxiety and/or depression in the presence of low, but at increased risk in the presence of high total childhood adversity. Respective gene–environment (G × E) interactions were found for (a) comorbid anxiety and depressive disorders (OR = 1.13), but neither pure anxiety nor pure depressive disorders and (b) pure/temporally primary anxiety disorders (OR = 1.07), but not pure/temporally primary depressive disorders. The G × E interaction remained associated with depressive disorders after introducing pure/temporally primary anxiety disorders as additional predictor (OR = 1.09). Conclusions: rs4606 alters the risk of developing a range of anxiety but also depressive disorders after childhood adversities. A complex risk pattern of genotype, environmental factors, and preexisting anxiety contributes to subsequent depression development.